The New Keynesian Model and the Long-Run Vertical Phillips Curve: Does It Hold for Germany? - Jan Gottschalk; Ulrich Fritsche (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
New-Keynesian macroeconomic models typically assume that any long-run trade-off between inflation and unemployment is ruled out. While this appears to be a reasonable characterization of the US economy, it is less clear that the natural rate hypothesis necessarily holds in a European country like Germany where hysteretic effects may invalidate it. Inspired by the framework developed by Farmer (2000) and Beyer and Farmer (2002), we investigate the long-run relationships between the interest rate, unemployment and inflation in West Germany from the early 1960s up to 2004 using a multivariate cointegration analysis technique. The results point to a structural break in the late 1970s. In the later time period we find for West German data a strong negative correlation between the trend components of inflation and unemployment. We show that this finding contradicts the natural rate hypothesis, introduce a version of the New Keynesian model which allows for some hysteresis and compare the effectiveness of monetary policy in these two models. In general, a policy rule with an aggressive response to a rise in unemployment performs better in a model with hysteretic characteristics than in a model without.
Keywords: C32; B22; E24; 330; Cointegration; Vector Error CorrectionModel; Unemployment; Phillips Curve; Hysteresis